Le Surréalisme dans l'Art - Legrand, Gérard (Paris : Département de la promotion et de la diffusion, 1982)
Duchamp, Marcel ; Man Ray ; De Chirico, Giorgio ; Ernst, Max ; Masson, André ; Miró, Joan ; Magritte, René ; Tanguy, Yves ; Bellmer, Hans ; Dali, Salvador ; Paalen, Wolfgang ; Lam, Wifredo ; Germinova, Maria ; Matta Echauren, Roberta
Frans
boek